Dynamika rozwoju biegów masowych w Polsce — analiza statystyczna - Waniowski, Tomasz; Żakowska, Sylwia (Wydawnictwo Uniwersytetu Wrocławskiego, 2018)
The quantitative development of mass-participation running events in Poland, especially in recent years, is huge. Nowadays, there are more than 4,000 runs organized every year and they are open for everyone. These running events have a different number of participants (from as little as 10 people, up to even a few thousands) and they are organized in many places by various institutions and organizations. Furthermore, we can distingusih long-distance runs (mainly marathons and half-marathons) and shorter-distance runs (e.g. 10 km). The aim of this of article is to analyze mass-participation running events in Poland statistically, taking into account many criteria: quantity, location, distance and sex. The following statistical methods are used: chain indexes and average annual rate of change. Statistical data were obtained directly from organizers, their websites and different publications about mass-participation running events in Poland. The authors present a versatile statistical view on Polish mass running events in tabular and chart forms
Keywords: mass-participation run; running events; statistical analysis; chain indexes; single-item indexes; average rate of change